PEMBANGKIT LISTRIK TENAGA GEMPA BUMI (PLTGB) : PEMANFAATAN GETARAN GEMPA BUMI SEBAGAI PENGHASIL ENERGI LISTRIK PASCA GEMPA YANG RAMAH LINGKUNGAN - yuniar amalia (Civil Infrastructure Engineering and Architectural Design, 2020)
Earthquakes are events that come suddenly. Until now, the occurrence of the earthquake has not yet been predicted. Likewise, the risk posed by earthquakes cannot be predicted, but can be reduced through disaster mitigation. However, mitigation has not been able to solve problems that occur after the earthquake, such as constraints on meeting electrical energy. Indonesia has the potential to utilize earthquake vibrations into electricity, through the Earthquake Power Plant (PLTGB) proposed by the author. One of the techniques that can be used for the process of converting earthquake vibration energy into electrical energy is using piezoelectric materials. Piezoelectric material is a material that has high advantages with a stable energy density and does not require an external power so that its utilization produces large profits. The process of harvesting electrical energy is obtained from applying pressure to the piezoelectric material at a certain frequency, so that the piezoelectric material can function as an electric generator. The type of writing used in this paper is literature review, with secondary data sources obtained from various literatures. Data collection techniques using documentation study. Data analysis used an interactive analysis model, namely data collection, data reduction, data presentation and drawing conclusions. The principle of PLTGB application is carried out in two periods, namely the period during the earthquake and the period outside the earthquake with the aim of storing energy reserves outside the earthquake. The PLTGB construction material is implanted under the highway at 5 meters near the zebra crossing which will be made like a bump, so that during the earthquake period the material will work as in principle. However, outside the earthquake period, when the vehicle stops or runs, it will put mechanical pressure on the piezoelectric which can generate electric current. The material to be used as a piezoelectric in PLTGB is Barium Titanate (BaTiO3). This material is based on normal ferroelectricity which is strong for transducer induction when compared to the magnitude of its polarization, the amount of permittivity, and the amount of stress induction that this material can reach. The first stage of PLTGB implementation is creating a pilot area, the second stage of evaluation, the third stage of promotion, the fourth stage of PLTGB socialization, and the fifth stage of developing PLTGB nationally. For Indonesia, PLTGB has the potential to be applied. It is hoped that the electrical energy produced by PLTGB can be used for post-earthquake activities.